Предмет: Алгебра,
автор: yli2008335
Решить уравнение: y=x^2+4x-3, f(x)=(x+1)*(2x-3), y=f(x)
Ответы
Автор ответа:
0
y = x^2+4x-3
f(x) = (x+1)*(2x-3)
y = f(x)
x^2 + 4x - 3 = (x+1)*(2x-3)
x^2 + 4x - 3 = 2x^2 - x - 3
x^2 - 5x = 0
x( x - 5) = 0
x = 0
x = 5
f(x) = (x+1)*(2x-3)
y = f(x)
x^2 + 4x - 3 = (x+1)*(2x-3)
x^2 + 4x - 3 = 2x^2 - x - 3
x^2 - 5x = 0
x( x - 5) = 0
x = 0
x = 5
Автор ответа:
0
x^2+4x-3=(x+1)*(2x-3)
x^2+4x-3= 2x^2-3x+2x-3
x^2+4x-3-2x^2+x+3=0
-x^2+5x=0
x^2-5x=0
x(x-5)=0
x=0 и x = 5
x^2+4x-3= 2x^2-3x+2x-3
x^2+4x-3-2x^2+x+3=0
-x^2+5x=0
x^2-5x=0
x(x-5)=0
x=0 и x = 5
Похожие вопросы
Предмет: Физкультура и спорт,
автор: xomyak2001
Предмет: Математика,
автор: Splyx02
Предмет: Русский язык,
автор: mortplay62
Предмет: Химия,
автор: bov1996
Предмет: История,
автор: вильдан123